Effects of Bean Ethanol Extract (Phaseolus Vulgaris L.) on Superoxide Dismutase Activity in Wistar Mice (Micetus Norvegicus) Hyperglycemia - Sinaga, Ade Putra Fratama; Ilyas, Syafruddin; Anggraini, Dwi Rita (Indonesian Journal of Medicine, 2017)
Background: Aloxan tetrahyd micee causes free radicals and higher reactive oxidative species (ROS) production, being able to lead to reduce insulin secretion from pancreatic ÃÂ² cells and receptor sensitivity in insulin-receptor cells resulting in hyperglycemia conditions. Bean extract ethanol can reduce oxidative stress. The purpose of this study was to determine beanÃ¢â¬â¢s ethanol extract effectiveness in lowering blood sugar levels and increasing the activity of superoxide dismutase (SOD) enzyme.Subjects and Methods: This was a randomized controlled trial (RCT) study. The samples were mice (Micetus norvegicus) of wistar strains randomized in five groups: P1-negative control, positive P2-control, P-3 ethanol extract group of 200mg / kgBW, P4-group 400mg / kgBW, P5-group 600 mg / kgBW. Dependent variables are blood sugar (mg/ dL) and superoxide dismutase enzymes. The independent variable is the bean extract of ethanol. Differences in blood sugar levels and superoxide enzyme levels of intergroup dismutase were tested by Anova test, followed by post hoc test, to determine the effectiveness of bean extract ethanol.Results: This study showed a statistically significant decrease in blood glucose levels after ethanol extract of green beans 600 mg / kg BW from day 14 to day 28 (p <0.05). This study did not show a decrease in blood sugar levels after ethanol extract of green beans 200 mg / kgBW and 400 mg / kgBW from day 7 until day 28 (p> 0.05). Giving ethanol extract of green beans did not affect the activity of superoxide dismutase enzyme (p = 0.830).Conclusion: Giving ethanol extract of green beans 600 mg / kgBW effectively decrease blood sugar in male wistar mice (Micetus norvegicus) from day 14 to day 28. Giving ethanol extract of green beans 200 mg/ kgBW, 400 mg / kgBW, and 600 mg / kgBW, is not effective to increase the activity of superoxide dismutase enzyme.Keywords: Phaseolus Vulgaris L., blood sugar level, superoxide dismutase enzymeCorrespondence:ÃÂ Ade Putra Fratama Sinaga. Masters Program on Biomedics, Faculty of Medicine, North Sumatra University. Email: adeputra535@ymail.com.Indonesian Journal of Medicine (2017), 2(2): 139-145https://doi.org/10.26911/theijmed.2017.02.02.08